337 Identification of Fecal Metabolites Associated with Fiber Exposure and Growth Performance in Growing-Finishing Pigs through Metabolomic Investigation. (10th April 2018) - Guo, J; Hu, Q; Faris, R J; Hung, Y T; Song, Y; Yao, D; Saqui-Salces, M; Urriola, P E; Shurson, G C; Chen, C
Abstract: High-fiber ingredients in swine feeds can decrease nutrient digestibility and growth performance, and therefore compromise their value as economic sources of energy and nutrients for pigs. Antibiotics and zinc treatments early in life have the potential to alter the metabolic responses of growing-finishing pigs to high fiber diets through the modification of gut microbiota and intestinal physiology. The identification of biomarkers that can associate the fiber exposure with growth performance as well as with other dietary treatments is highly desirable for many applications. In this study, 128 pigs were divided into four groups (32 pigs/group) in the 43-day nursery phase, and fed with/without antibiotic (Carbadox, 0 vs. 55 ppm) and low/high concentration of zinc oxide (ZnO, 150 vs. 2500 ppm). Antibiotics treatment lasted the entire nursery phase while ZnO treatment ended on the 21 day of the phase. In the 100-day growing-finishing phase, Carbadox was replaced by Bacitracin (27.5 ppm) in the antibiotic treatment, and 4 treatment groups in nursery phase was further divided to 8 groups (16 pigs/group) based on low/high level of fiber (wheat middings, 10-15% vs. 25-55%) in the feeds. Growth performance data were analyzed using PROC Mixed in SAS, with treatments as fixed effects and block as random effect. High fiber diet decreased the ADG (P < 0.01) and G:F ratio (P < 0.01) while ZnO and antibiotics treatments had no effect on growth performance. Interaction on growth performance was not observed among fiber, ZnO, and antibiotics. Liquid chromatography-mass spectrometry (LC-MS)-based metabolomic analysis of fecal samples collected on day 30 of growing-finishing phase showed that fiber treatment, but not antibiotics or ZnO, led to the sample separation in the principal components analysis (PCA) models of fecal metabolome. Subsequent quantitative analysis revealed that high-fiber treatments affected multiple fatty acids (including dodecanoic acid, pentadecanoic acid, and palmitoleic acid), amino acids (including alanine, glutamine, and threonine), bile acids (including cholic acid, taurocholic acid, and deoxycholic acid) and lysophospholipids in feces. These results suggest that fiber treatment had much greater influences on the fecal metabolome of finishing pigs than antibiotics treatment and ZnO pretreatment. Further studies are warranted for investigating the contributions of these fiber-induced metabolic changes on growth performance.